Siapakah yang Kamu Cari?: Suatu Analisis atas Kisah Penangkapan Yesus dalam Yohanes 18:1-11 - Yulianus Niba (IAKN Ambon, 2021)
This study attempts to analyze the Story of the Arresting of Jesus in John 18:1-11. The aim is to explore the meaning contained in this scene, more specifically related to Jesus' question